2020
DOI: 10.1177/0960327120937048
|View full text |Cite
|
Sign up to set email alerts
|

Crocin attenuates CCl4-induced liver fibrosis via PPAR-γ mediated modulation of inflammation and fibrogenesis in rats

Abstract: Background: Liver fibrosis is a chronic pathological condition with a leading cause of liver-related mortality worldwide. In the present study, we have evaluated the antifibrotic effect of crocin, a carotenoid present in the stigma of Crocus sativus, and also explored its putative mechanism of action. Methods: Liver fibrosis was induced by intraperitoneal administration of 30% carbon tetrachloride (CCl Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…showed that crocin decreased the hepatic fibrosis via expression of peroxisome proliferator-activated receptor γ (PPAR-γ), modulating the inflammatory and fibrogenic pathways. 83 These results are consistent with another study showing the anti-fibrotic and anti-inflammatory properties of crocin in thioacetamide (TAA)-induced liver fibrosis. 47 …”
Section: Discussionsupporting
confidence: 92%
“…showed that crocin decreased the hepatic fibrosis via expression of peroxisome proliferator-activated receptor γ (PPAR-γ), modulating the inflammatory and fibrogenic pathways. 83 These results are consistent with another study showing the anti-fibrotic and anti-inflammatory properties of crocin in thioacetamide (TAA)-induced liver fibrosis. 47 …”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we found that GDFMD could effectively reverse the abnormal expression of 20 genes in WD; among these the expression of 18 genes (Apoa2, Acaa1b, Acsl1, Acox1, Ppara, Fads2, Scd2, Slc27a2, Pck1, Hmgcs2, Cyp7a1, Cyp4a31, Cyp4a14, Slc27a5, Slc27a1, Scd1, Cyp8b1, and Fabp1) was low and that of 2 genes (Cyp4a32 and Cyp4a10) was high in the Model group. A large body of evidence suggests that PPAR signaling pathway is involved in different liver diseases (Panebianco et al, 2017;Zhang et al, 2020), especially liver fibrosis (Chen et al, 2015;Pawlak et al, 2015;Chhimwal et al, 2020), as was also confirmed in the present study. Our results show that GDFMD can alleviate liver damage in WD by reversing the changes in the PPAR signaling pathway (Figure 8).…”
Section: Discussionsupporting
confidence: 89%
“…It has also been confirmed that PPAR-γ plays a strong role in inhibiting liver fibrosis by cross-talk with inflammatory-related factors, such as NF-κB and AP-1, inhibiting T cell activation and macrophage proliferation and secretion. 4 , 28 , 38 , 39 …”
Section: Mechanisms Underlying Hepatic Fibrosis and Ppar-γmentioning
confidence: 99%
“… 78 Crocin treatment significantly reduces the serum liver enzyme level and improves liver CYP2E1 mRNA levels and the pathologic changes of liver tissue. 38 The alcohol extract of Rhus verniciflua fruit can prevent liver fibrosis induced by carbon tetrachloride in mice by inhibiting inflammatory factors [83]. Lycopene inhibits HSC activation, and regulates cell lipid storage and signal transduction.…”
Section: Ppar-γ Targets Anti-fibrosis Drugsmentioning
confidence: 99%
See 1 more Smart Citation